Learning and value formation in teaching by peer tutoring - Benoit Ríos, Claudine Glenda; Jaramillo Azema, Cristian Alonso; Castro Cáceres, Ricardo Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The teaching-learning process requires the active participation of students throughout different stages of their academic work and their ability to adapt to the system requirements. In the face of these challenges, educational institutions promote the use of different pedagogical strategies. Peer tutoring is one of these strategies, which is based on collaborative working between tutors and tutees. In this context, the present article seeks to describe ten tutors’ perception concerning the implementation of a peer tutoring program at a University in the Bío Bío Region in Chile, and to identify the strategies implemented to support low-performing students. On the basis of a qualitative method, the results of the research visualize the evaluation carried out by tutors regarding the program participants’ skills and values which can be enhanced, including solidarity, empathy, the ability to give relevant advice to the tutees, strengthening of knowledge in a bidirectional way, tutors’ mastery of subject matter and their practice as future teachers.